Low-Latency Edge Computing for Real-Time Applications in Wireless Sensor Networks - Mishra, Awakash; Rathour, Abhinav; Raju, Dheeravath; Patil, Shashikant; Muthiah, M.A.; Patra, Bichitrananda; Kalidhas, Aravindan Munusamy (International Journal of Engineering, Science and Information Technology, 2025)
Real-time data processing with Edge Computing, such as Low Latency Edge Computing (LLEC), allows for functioning at the network boundary or edge, which enhances responsiveness and reduces latency in WSNs. This approach is helpful for most time-critical needs in innovative city applications, healthcare, industrial automation, and other areas where prompt actions are crucial. In contrast to conventional cloud models, LLEC processes data at the collection site to reduce the transmission time, improving bandwidth efficiency. Moreover, LLEC increases the height of scalable walls and energy efficiency by shifting the computational burden to the edge nodes. This document focuses on the most critical problems in WSNs, such as restricted resources, limited scalability, and security issues. We offer a distributed edge framework with real-time processing features and minimal security protocols to address these gaps. Localized computation at cluster heads diminishes network congestion while prolonging sensor life. This paper presents multiple case studies demonstrating LLEC's effectiveness in practical applications. Finally, the paper discusses the widening scope of research and the importance of LLEC in future distributed systems.